Avlsten - Glob, P.V. (Kuml, 1959)
Forge-stones - New Types from the Danish lron Age. Among many subjects treated during a long lifetime of research, Professor Gudmund Halt has also dealt with the production of iron 1). On many points his researches have extended our knowledge of the blacksmith and his work, but new discoveries are continually being made which widen our acquaintance with this important side of lron Age craftsmanship. In this article will be described two new tools from the blacksmith's workshop, two forge-stones which had their place on the forge, as shields for the spout of the bellows, both of them unusual in shape, ornamentation and material. The first of these forge-stones (Fig. 2) was found in the spring of 1950 on the beach by Snaptun in Horsens Fjord; the second (Fig. 7) is of unknown provenance, but probably from Jutland. The forge-stone from Snaptun is made of steatite (fatstone or soapstone), a greyish green stone which is so soft that it can easily be cut or sawn out of the cliff and can be carved with a penknife. But at the same time it is fire and acid-proof, and resistant to weathering, and it was therefore used in antiquity, as early as the Bronze Age, as a suitable material for casting moulds, and later, during the Iron Age, for making forge-stones and cooking pots 6). This type of stone does not occur in Denmark, but is found in many places in Norway, where several steatite quarries from the Viking Period have been identified, some with unfinished containers still attached to the living rock 7). The Snaptun stone is the most beautifully fashioned forge-stone known. It is finely shaped with an evenly curved front, decorated with a carved man's face (Fig. 2a), a rounded top curving slightly outwards to the massive base, and a back whose regular shape is emphasized by a broad carved groove, which follows and brings out the contour of the stone. The hole for the spout of the bellows is surrounded by a raised ring which merges into the base (Fig. 2b). The stone is 20 cms. tall, 24.5 cms. wide, and 7.5 cms. thick. Beneath the man's face can be seen the blow-hole, measuring 1.2 X 1.5 cms. and surrounding by slight traces of fire, while at the rear, where the spout of the bellows has been inserted, the hole is somewhat larger, 1.7 X 1.8 cms. The ornamentation, and similar specimens from Norway, date the Snaptun stone to the Viking Period. Men's faces, of related type but by no means identical, are known from several rune stones in Jutland and Sweden 8), but as the forge-stone is probably Norwegian an exact correspondance with these masks, which in addition are carved in other kinds of stone, can hardly be expected. All these figures belong to the Late Viking Period. The Snaptun stone finds its closest parallels in a series of Norwegian forge-stones of the same material and size, several of which come from graves of the Viking Period. But two specimens are also known from the foregoing period, of a different and more tubular shape, though with a cross-section of the same shape as the Snaptun stone 13). In his article on forge-stones Sigurd Grieg emphasizes that the shape of the forge-stones is so varied that the specimen illustrated by O. Rygh from Vik as a typical example is in fact only a single form among many different types 14). But since that time the amount of material has increased, so that now the Vik stone in fact forms an excellent type-specimen (Fig. 4). It is undecorated, with clear traces of fire around the blow-hole, and is somewhat smaller than the Snaptun stone. On a basis of the burial in which it was found it can be dated to the Early Viking Period, perhaps as early as the beginning of the 9th century 15). Two further forge-stones of this type, of the same material and without ornamentation, are known from Norway. One was found at Finnestad in Rakkestad 16), and the other in Storhaugen on Haugland, the latter together with objects including an axe of Late Viking Period type 17). Two other specimens, on the other hand, are ornamented. The first of these was found among remains of charcoal and stone cairns on a little rise at Haugsvol in Østfold; it bears two bands with circles and chevrons around the blowhole, which shows considerable traces of fire, while on the back there is a similar band of rougher workmanship, as well as circles around the hole (Fig. 5) 18). The second, discovered together with a spearhead in a tumulus near Øvrebö in Rogaland, is of a somewhat different type with, on the top, a field of decoration comprising four chevrons each containing three round knobs (Fig. 6). The same type of ornamentation as on this forge-stone is found on a bronze brooch from Norland 19). The brooch is dated to the 8th century by Shetelig, who also records that it belongs to a Trønder group 20). This forge-stone thus appears to belong to the century before the beginning of the Viking Period, a conclusion which would be in agreement with its shape, which is wider and lower than the type described above, and thus typologically would lie between the tubular type21) and the Vik type. The Norwegian discoveries thus confirm that forge-stones of the Vik type were in use both in the Early and the Late Viking Period. The method by which they were attached to the bellows and the forge can be seen in pictures of somewhat later date, which in addition show that the type remained in use after the close of the Viking Period. On the Sigurd carving at Ramsundsberget north of Eskilstuna a forge-stone can be seen in position on the tip of a bellows, but its type cannot be determined with full certainty (Fig. 1). If it be permitted to assume that the stone was drawn in oblique perspective it might well be of the Vik type, and in that case this type was in use in Sweden in the 11th century, though otherwise only round and rectangular forms are known from Iron Age discoveries in that country 22). A more definite reproduction of the type here described is given by the group, also from the saga of Sigurd Fafnersbane, on the carved wooden portal of Hylestad church in Setesdal in Norway (cf. cover picture). In the lowest register a forge-stone can be seen from the side, with the bellows at work blowing air through the forge-stone into the hearth, while Regin the smith works before the anvil. Forge-stones of the Vik type were thus in use in Norway in the Viking Period and in the Middle Ages, and the stone from Snaptun must be ascribed to this period of time. The other forge-stone, similarly of steatite, is of rectangular type (Fig. 7). It is 9.8 cms. long, about 5 cms. tall, and 6.9 cms. wide at the front and 6 cms. at the back. There the spout of the bellows has been inserted in a hole measuring 2.2 cms. in diameter and narrowing to 1 cm. at the front, where the stone is burnt red, showing much trace of fire. On the top it bears a shallow design of interlacing bands, framed by a single line. The shape and ornamentation of the stone makes a dating possible. For the same type, though of baked clay, is known from a burial at Ekeby in Södermanland which must be dated to the time around 500 AD 27). The Ekeby specimen, considerably burnt at the end at which the hole is smallest, is of about the same dimensions as the one here described, as it is quoted as being 10.5 cms. long, about 8 cms. wide and 5.5 cms. high. The stone is unfortunately so worn on the upper surface that its ornamentation can no longer be clearly made out, but it appears to comprise an irregular pattern of interlacing bands. It would thus appear probable that the Danish specimen should be dated to the 6th century. The two forge-stones here described are the only ones known from Denmark, and both appear to belong to the Late Iron Age. As the use of bellows in forging metal was known from at latest the beginning of the Early Iron Age, since a wooden spout for a double bellows is known from the Hjortspring discovery 31), some other type of shielding for the bellows spout against the flame of the hearth must have been in use. Clay spouts for this purpose have also in two cases been found. One of these specimens is a conical, slightly curved clay tube with the tip broken off; its surviving length is 19 cms., and it was found standing point upwards on a hearth in a field in Tyregod parish in central Jutland. It has been ascribed to the later part of the Bronze Age by reason of the type of pottery of which it is composed 32), but this dating cannot be regarded as in any way certain. The other clay tube comes from a house site of Early Roman Iron Age date at Præstevang, Øster Hornum parish, Aalborg county. This specimen, which lay by a hearth in the west end of a house lying east-west, is 12.7 cms. long and funnel-shaped, being about 11.5 cms. in diameter at the broad end and 2.9 cms. at the narrow (Fig. 8) 34). The clay is about 1 cm. thick and hard-fired, and the hole at the narrow end is about 1.7 cms. in diameter. As the point is not noticably marked by fire, this example must either be an unused specimen, or else has been used for some other purpose than the protection of the spout of a bellows. It may have been used as a funnel, though funnels are not otherwise known from this period. That the prehistoric periods in Denmark are only able to produce these few examples of clay spouts for bellows is doubtless due to the fact that such spouts would in the course of the work burn completely to fragments and would be continually replaced by new, which in turn suffered the same fate. P. V.Glob